Dissecting pseudoneglect in real and virtual environments: effects of tool and stimulus, not distance or environment. - Moultaka, Dalya; Bouchara, Tifanie; Guilbert, Alma (Laterality, 2026)
Pseudoneglect is a spatial bias favoring the left side of space observed in healthy individuals, typically shown by a leftward deviation when bisecting horizontal lines. Although environmental and individual factors are known to modulate this bias, findings remain inconsistent. This study aimed to provide new insights into the influence of four environmental factors on pseudoneglect: Distance (near, far), Environment (real, immersive Virtual Reality (iVR)), Tool (pen, laser pointer), Stimulus (line, object), while controlling handedness. Fifty-five participants (M = 20.6 years, SD = 2.3, 35 right-handed) completed three line bisection tasks in a real environment (paper-and-pencil at near distance, laser at near and far distances) and three in iVR: (laser at near and far distances, French baguette bisection at near distance). A significant Tool effect emerged: pseudoneglect appeared only in the paper-and-pencil bisection task, while a rightward bias observed with a laser pointer. Stimulus also had a significant effect, with a more rightward bias for the baguette than for lines. No main effects of Distance, Environment, or Handedness were found. Several interpretations are discussed, such as inter-individual variability, coding of peripersonal and extrapersonal spaces, and interaction between semantic and attentional networks. Our results emphasize the need to homogenize methodologies across studies.